An international laboratory comparison of dissolved organic matter composition by high resolution mass spectrometry: Are we getting the same answer?. (5th June 2020) - Hawkes, Jeffrey A.; D'Andrilli, Juliana; Agar, Jeffrey N.; Barrow, Mark P.; Berg, Stephanie M.; Catalán, Núria; Chen, Hongmei; Chu, Rosalie K.; Cole, Richard B.; Dittmar, Thorsten; Gavard, Rémy; Gleixner, Gerd; et al.
Abstract: High‐resolution mass spectrometry (HRMS) has become a vital tool for dissolved organic matter (DOM) characterization. The upward trend in HRMS analysis of DOM presents challenges in data comparison and interpretation among laboratories operating instruments with differing performance and user operating conditions. It is therefore essential that the community establishes metric ranges and compositional trends for data comparison with reference samples so that data can be robustly compared among research groups. To this end, four identically prepared DOM samples were each measured by 16 laboratories, using 17 commercially purchased instruments, using positive‐ion and negative‐ion mode electrospray ionization (ESI) HRMS analyses. The instruments identified ~1000 common ions in both negative‐ and positive‐ion modes over a wide range of m / z values and chemical space, as determined by van Krevelen diagrams. Calculated metrics of abundance‐weighted average indices (H/C, O/C, aromaticity, and m / z ) of the commonly detected ions showed that hydrogen saturation and aromaticity were consistent for each reference sample across the instruments, while average mass and oxygenation were more affected by differences in instrument type and settings. In this paper we present 32 metric values for future benchmarking. The metric values were obtained for the four different parameters from four samples in two ionization modes and can be used in future work to evaluate the performance of HRMS instruments.